2016
DOI: 10.3382/ps/pew108
|View full text |Cite
|
Sign up to set email alerts
|

The role of metabolic state and obestatin in control of chicken ovarian hormone release

Abstract: The aim of the present study was to examine the role and interrelationships between calorie restriction and obestatin in the control of hormone release by chicken ovarian tissue. For this purpose, we compared the release of progesterone (P), testosteron (T), estradiol (E), and arginine-vasotocin (AVT) by ovarian fragments isolated from chicken subjected and not subjested to food restriction, as well as the response of these ovarian fragments to obestatin additions.It was observed that food restriction promoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Nutrition affects the secretion of reproductive hormones and the concentration of metabolic substrates in blood. Research showed that food restriction promoted release of P4, reduced out of the T, but did not affect E release, suggesting that metabolic status can control the release of these hormones [32]. The estrogen estradiol-17ß is known as one of the major gonadal steroid hormones with different functions in reproduction [33].…”
Section: Factors Related To the Metabolic And Nutritional Statusmentioning
confidence: 99%
“…Nutrition affects the secretion of reproductive hormones and the concentration of metabolic substrates in blood. Research showed that food restriction promoted release of P4, reduced out of the T, but did not affect E release, suggesting that metabolic status can control the release of these hormones [32]. The estrogen estradiol-17ß is known as one of the major gonadal steroid hormones with different functions in reproduction [33].…”
Section: Factors Related To the Metabolic And Nutritional Statusmentioning
confidence: 99%
“…Feeding quails with a seed mixture instead of the usual mixed feed causes an increase in HPCA activity and corticosterone response [96]. As a result of limited feeding, ovarian tissue of hens excreted in vitro more progesterone and less testosterone while secretion of 17β-estradiol and arginine vasotocin did not change [97]. In the hypothalamus and ovary of 23-week-old individuals, expression of grehlin and its receptors was activated.…”
mentioning
confidence: 99%